Digital Mediation of the Quran and Transformation of Religious Literacy in the Modern Southeast Asia: A Critical Analytical Review - Shehar Bano; Waqeem Akram (Indonesian Journal for Islamic Studies, 2026)
The article focuses on the critical analysis of how digital media mediate the activities involving engagement with the Quran and how it changes the religious literacy in modern Southeast Asia. The scholarship of the study on digital religion, interdisciplinary scholarship in Islamic studies, and the theory of religious literacy analyzes the impacts of mobile Qur'an applications, social media platforms, and online educational initiatives on the transformation of Quranic access, interpretation, as well as authority. The paper constructs a multidimensional system of digital Quranic religious literacy, including textual, interpretive, ethical, and authority-related competencies through a qualitative/critical analytical method using secondary literature. The study shows that digital mediation has contrasting literacy results, which are influenced by platform logic, institutional regulation, language, and local culture, using a comparative analysis of Indonesia and Malaysia. Even though digital media provide opportunities for increased accessibility and informal and lifelong Quranic education, particularly among young people, they bring about chances of fragmentation, insufficient engagement, and inadequate scholarly mediation. It should be reflected in the article that digital transformation does not displace classical Islamic epistemology and does not presuppose a rise of literacy, but, on the contrary, one must integrate pedagogies, govern ethically, and find a new interpretive responsibility. The research has a theoretical and regional contribution to the discourse on digital religion and education in Islam and religious authority.